Tests of the possible social significance of ’nonsense’ orientation - Matthews, G V T (Wildfowl, 1962)
To test whether ’nonsense’ orientation was concerned with the reassembly of a scattered flock, large numbers of Mallard were released in groups of varying sizes. Groups proceeded N.W. rather more strongly and directly than single birds and over a certain size the groups tend to break up. This argues against the orientation behaviour being group-seeking. Single birds released to the north of, but close to, the roosting site still showed N.W. orientation, indicating that regaining the roost is not of paramount importance. The question of the importance of landmarks to the individual would repay further investigation.